Importance of the indian constitution's guiding principles for government policy: Exploring the Impact and Significance of Directive Principles in Indian Government Policy (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Directive Principles have been codified as part of the Constitutional Law precisely because theirscope extends beyond political democracy to include social and economic liberalism. They are put inplace to serve as a Instrument of Instructions for the Governance of the Country, with the hope thatfuture lawmakers and administrations might learn from the precedent they create. It has a major place inthe Constitution since it was crucial in guiding the State to create equitable economic and socialcircumstances for all Indians.